SB-DRED: a novel congestion control algorithm for H.264 video streaming over 802.11e. (17th January 2013) - Lai, Wen-Ping; Liou, En-Cheng
The IEEE 802.11e EDCA provides differentiated service for multimedia transmission via in-station multiple access category (AC) queues and virtual collision handling for wireless channel access contention. However, the FIFO nature of AC_VI (AC for Video) limits its performance. To provide further service differentiation among video packets, this paper presents a novel cross-layer design called E-DVFI+SB-DRED, i.e. equal-population-grouping of dispersive-video-frame-importance (E-DVFI) for a precise video importance scheme in the Application layer and segmented-and-bounded dispersive-random-early-detection (SB-DRED) in the MAC layer for a hyperfine video packet mapping algorithm among AC_VI and its lower-priority ACs. PSNR-based performance evaluations and comparisons including the effects of video input rate to AC_VI and cross-traffic via the other ACs have been considered over reference video sequences, and the results show that the proposed cross-layer design consistently outperforms the existing ones, including EDCA, I/P+AM, and our previous study DVFI+DRED.